ChemInform Abstract: Phosphinite‐Iminopyridine Iron Catalysts for Chemoselective Alkene Hydrosilylation. Issue 26 (1st July 2014) - Peng, Dongjie; Zhang, Yanlu; Du, Xiaoyong; Zhang, Lei; Leng, Xuebing; Walter, Marc D.; Huang, Zheng
Abstract The title catalysts are efficient and selective for the anti‐Markovnikov alkene hydrosilylation of primary, secondary, and tertiary silanes.